Differences in HIV infection trends in two regions of Cameroon with a longstanding HIV epidemic: insights from 2012 and 2022 - Ngoume, Yannick F.; Teagho, Urmes C.; Eselacha, Brice; Goni, Oumarou H.; Kenfack, Dell-Dylan; Tchakoute, Mérimé; Nguefack-Tsague, Georges; Tongo, Marcel (Frontiers in Public Health, 2025)
IntroductionTo achieve the UNAIDS 95-95-95 target by 2025, it is of great importance to test and diagnose individuals infected with HIV; especially those residing in communities with limited access to health and in areas with a longstanding HIV epidemic, where the virus has been circulating since the early phase of the pandemic. In this regard, we determined the HIV prevalence in remote communities of the East and South administrative regions of Cameroon where the four cross-species SIV transmissions that gave rise to the four HIV-1 groups likely happened.MethodsWe did this in two different periods: 2012/2013 (Period 1; 4,435 participants enrolled in the East and 2,347 in the South) and 2021/2022 (Period 2; 2,203 participant enrolled in the East and 2,347 in the South) using HIV1/2 rapid assays and standard ELISAs and according to the WHO testing strategy.ResultsDuring Period 1, the HIV seroprevalence in the East was 6.9%. This prevalence had significantly decreased to 2.7% [Prevalence Difference or PD: 4.1 (3.1; 5.2); p < 0.001] by Period 2. Contrasting with these results, the HIV prevalence in the South during Period 1 was 5.5% and did not significantly change by Period 2 at 5.2% [PD: 0.3 (1.07;1.6); p = 0.67].ConclusionOur data suggest that HIV transmission in remote communities of the South administrative region of Cameroon has likely remained uncurbed over the past decade. As a result, this region should be prioritized in efforts to curb the spread of HIV and reduce its prevalence.